Aortic thrombosis in COVID-19 - Wickham, H; Tam, JCH; Chan, XHS; George, MJ; Levi, M; Brown, M (Elsevier, 2020)
Background Venous thrombo-embolism is now well-recognised as a common complication of severe COVID-19 disease. Arterial thrombosis has been less well recognised, although it is increasingly reported, mostly in the context of myocardial infarction and stroke.